«ҚАРАҚАЛПАҚ ТИЛИНИҢ ЖАҢА ТАРИЙХЫ БОЙЫНША ОЧЕРКЛЕРИ» ҲАҚҚЫНДА - Аманбаев, Б. (FAN va JAMIYAT, 2022)
This article examines the history of the development and formation of the Karakalpak language by turkologists, as well as their weightless contribution to the development of turkic languages, in particular, the Karakalpak language. Special attention is paid to N.Baskakov, the theorist and founder of the Karakalpak grammar. As well as the transition of karakalpak graphics from arabic to latin and cyrillic.